2014
DOI: 10.1002/ajoc.201402224
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Catalysis of the Aerobic Baeyer–Villiger Oxidation over a Bifunctional Catalyst Based on Cobalt Tetraphenylporphyrin Intercalated into Zn2Al Hydrotalcite

Abstract: Scheme 1. The reaction steps for B-V oxidation with an O 2 /aldehyde system.[a] Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Horizontal and perpendicular intercalations of metalloporphyrins inside different materials are known [ 42 , 44 , 45 ]. Diagonal orientations have also been reported inside niobite Nb 3 O 8 − [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Horizontal and perpendicular intercalations of metalloporphyrins inside different materials are known [ 42 , 44 , 45 ]. Diagonal orientations have also been reported inside niobite Nb 3 O 8 − [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al reported that anionic metalloporphyrins were intercalated inside layered double hydroxides in a perpendicular orientation [ 27 ]. Metalloporphyrins intercalated inside layered double hydroxides have been witnessed earlier [ 20 , 28 ]. Tubular halloyasites have also been described for metalloporphyrin intercalation purposes [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that acetic acid can be used as a protic acid, which may activate cyclohexanone in the catalytic reaction and accelerate the progress of the reaction. [22] 4 A-MS is a kind of desiccant commonly used in laboratories which with many Lewis acid sites. The conversion of BÀ V oxidation was enhanced because the Lewis acid sites of 4 A-MS activated cyclohexanone and benzaldehyde.…”
Section: Solvent T [°C] Time [H]mentioning
confidence: 99%
“…They found co-catalysts such as SiO 2 , 4 A molecular sieve (MS) could significantly enhance the selectivity of ɛ-caprolactone and reduce the amount of benzaldehyde additive. [20] Iron porphyrin based heterogeneous polymer catalyst FCMP-1 [21] was also effective for BÀ V oxidation and cobalt porphyrin catalyst CoTSPP-Zn 2 Al-LDH [22] may even obtain ɛ-caprolactone as high as 98 % yield. Hybrid porphyrin-heteropolyacid material FPOP also proved active in the BÀ V oxidation of cyclohexanone.…”
Section: Introductionmentioning
confidence: 99%
“…He 153 applied catalyst 49Co (Figure 8) in Baeyer−Villiger oxidation reaction for several cyclic ketones to lactones using benzaldehyde as co-catalyst, at 40 °C, over 7−14 h (Scheme 34). The authors proposed the involvement of peroxybenzoic acid as oxidant, resulting from the in situ oxidation of benzaldehyde with O 2 , yielding the desired lactones in very high yields.…”
Section: Homogeneous Versus Heterogeneous Oxidation Reactions Catalyz...mentioning
confidence: 99%